2017
DOI: 10.1007/s11892-017-0922-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of One-Step IADPSG Versus Two-Step Diagnostic Criteria for Gestational Diabetes in the Real World: Impact on Health Services, Clinical Care, and Outcomes

Abstract: Purpose of ReviewThis paper seeks to summarize the impact of the one-step International Association of Diabetes and Pregnancy Study Groups (IADPSG) versus the two-step gestational diabetes mellitus (GDM) criteria with regard to prevalence, outcomes, healthcare delivery, and long-term maternal metabolic risk.Recent FindingsStudies demonstrate a 1.03–3.78-fold rise in the prevalence of GDM with IADPSG criteria versus baseline criteria. Women with GDM by IADPSG criteria have more adverse pregnancy outcomes than w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 75 publications
4
71
0
3
Order By: Relevance
“…The reported figure for frequency of GDM goes in hand with Ma et al (30) , Karcaaltincaba et al (31) and Arbib et al (32) who reported frequencies of 12.2%, 11.1% and 9.9%, respectively for GDM. Moreover, Huhn et al (33) and Brown & Wyckoff (34) documented that the introduction of the IADPSG criteria resulted in an absolute increase of GDM prevalence of 8.5% (33) and a 1.03-3.78-fold rise versus baseline criteria (34) .…”
Section: Discussion:-mentioning
confidence: 99%
“…The reported figure for frequency of GDM goes in hand with Ma et al (30) , Karcaaltincaba et al (31) and Arbib et al (32) who reported frequencies of 12.2%, 11.1% and 9.9%, respectively for GDM. Moreover, Huhn et al (33) and Brown & Wyckoff (34) documented that the introduction of the IADPSG criteria resulted in an absolute increase of GDM prevalence of 8.5% (33) and a 1.03-3.78-fold rise versus baseline criteria (34) .…”
Section: Discussion:-mentioning
confidence: 99%
“…For offspring, GDM pregnancy confers a greater risk of developing obesity, diabetes, hypertension, cardiovascular disease in youth, and adult life ( 6 , 7 ). According to the diagnostic criteria of 2011 issued by the Ministry of Health (MOH) China ( 8 ), which endorsed the new criteria by the IADPSG ( 1 ), the prevalence of GDM in China is 17.5% in 2013 ( 9 ), which is higher than the prevalence in Europe and the USA ( 10 , 11 ). Given the substantial relevance of GDM for medium and long-term health of both mother and offspring, it is crucial to identify modifiable risk factors which contribute to GDM prevention among Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…El diagnóstico de DMG ha sido tradicionalmente tema de controversia (39). La prevalencia del diagnóstico de DMG se ha incrementado con la difusión de los criterios de la IADPSG (40). En la revisión de la literatura, Brown et al reportan una prevalencia de DMG que varía entre 3,5 y 45,3 %.…”
Section: Discussionunclassified